A study on customer satisfaction towards service quality : Novotel Kota Kinabalu 1Borneo hotel room - Alimin, Nur Atikah (2013)
This study is about customer satisfaction towards the service quality of Novotel Kota Kinabalu 1 Borneo hotel room. This research was carried out at the hotel and it is based on quantitative approach. There are 50 questionnaires being distributed to the customers during check-in time and returned to the front desk at check-out time. In addition, this study also reviews related literature such as hospitality industry, customer satisfaction, service quality and hotel accommodations. This study also collects secondary data from Novotel Kota Kinabalu 1 Borneo management such as the room information. Therefore, based on finding and analysis of this study, the research objective has been achieved whereby the level of customer satisfaction towards service quality of Novotel Kota Kinabalu 1 Borneo Hotel Room is at Level 4 which is "Satisfied". In addition, there are 9 categories of hotel room independent variable that consists of the Cleanliness of Room, Cleanliness of Bathroom, Quality of Room's Facilities, Quality of Bathroom's Facilities, Quality of Room's Amenities, Quality of Bathroom's Amenities, Interior Design of Room, Interior Design of Bathroom and Service Quality of Bathtub. Furthermore, the most "Strongly Satisfied" independent variable of hotel room is the "Interior Design of Room" category. However, the most "Unsatisfied" level is the "Service Quality of Bathtub" category and the "Cleanliness of Bathroom" category.